2020
DOI: 10.1007/s10096-020-03857-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of berberine chloride and/or its combination with vancomycin on the growth, biofilm formation, and motility of Clostridioides difficile

Abstract: This study aims to investigate the antimicrobial and antibiofilm activity of berberine chloride (BBR) and vancomycin (VAN) as well as synergistic combinations of BBR with VAN against Clostridioides difficile strains. The effect of different concentrations of BBR on strain motility was also assessed. Twelve C. difficile strains (two reference C. difficile 630, ATCC 9689, and one control M120, and 9 clinical C. difficile strains belonging to the PCR-ribotype (RT027)) were collected and investigated for their sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
2
14
0
Order By: Relevance
“…coli decreases with prolonged exposure time [ 38 ]. In addition, BBR has direct inhibitory effects on bacteria such as Clostridium difficile , Actinobacillus , and Bacillus subtilis [ [39] , [40] , [41] ]. These studies indicate the direct antibacterial activity of BBR.…”
Section: Bbr Directly Regulates Gut Microbiotamentioning
confidence: 99%
“…coli decreases with prolonged exposure time [ 38 ]. In addition, BBR has direct inhibitory effects on bacteria such as Clostridium difficile , Actinobacillus , and Bacillus subtilis [ [39] , [40] , [41] ]. These studies indicate the direct antibacterial activity of BBR.…”
Section: Bbr Directly Regulates Gut Microbiotamentioning
confidence: 99%
“…When berberine chloride combined with penicillin, clindamycin, and erythromycin, can also significantly inhibit the growth of Streptococcus oralis in a dose-dependent manner. Further, when combined with vancomycin, it can greatly inhibit the growth and motor capacity of Clostridium difficile, and can synergistically inhibit drug-resistant C. albicans when paired with fluconazole (Dziedzic et al, 2015;Wultanska et al, 2020;Yong et al, 2020). Khameneh et al (2015) demonstrated that the co-application of piperine and gentamicin nanoliposomes on MRSA had a significant synergistic antibacterial effect.…”
Section: Alkaloids Combined With Antibiotics For Antibacterial Effectsmentioning
confidence: 99%
“…Currently, metronidazole and vancomycin are the most commonly used treatments against mild CDI; however, metronidazole is only recommended as an alternative treatment because metronidazole-resistant strains are emerging [ 200 , 243 ]. In addition, berberine chloride, which is used to treat diarrhea, also synergistically induced biofilm formation with vancomycin [ 244 ]. Unlike vancomycin and metronidazole, the recently approved antibiotic to treat CDI, fidaxomicin, was able to disrupt in vitro colony biofilms [ 191 ].…”
Section: What Induces Biofilm Formation?mentioning
confidence: 99%